124 Polyclonal Antibody Preparations from Avian Origin Increased Fiber Digestibility of Beef Cattle Receiving a Backgrounding Diet. (28th November 2020) - da Silva, Gleise Medeiros; Schulmeister, Tessa M; Tarnonsky, Federico; Podversich, Federico; Garcia-Ascolani, Mariana Eloisa; DiLorenzo, Nicolas
Abstract: This study investigated the effects of feeding an avian-derived polyclonal antibody preparation (PAP; CAMAS, Inc.) against Streptococcus bovis, Fusobacterium necrophorum, and lipopolysaccharides (40, 35, and 25% of the preparation, respectively) on plasmatic haptoglobin and glucose concentrations (Exp. 1), and apparent total tract digestibility (Exp. 2) of beef cattle consuming a backgrounding diet. In Exp. 1, Angus crossbreed heifers and steers (n = 90; 373 ± 62 kg BW) were randomly assigned to receive a common ad libitum diet (76% TDN, 15.9% CP, DM basis) with the addition of 1 (PAP1), 3 (PAP3), or 0 g (CON) of PAP daily. Plasmatic concentrations of glucose and haptoglobin were measured on d 0, 14, 28, 42, and 56. In Exp. 2, 25 Angus crossbreed steers (390 ± 65 kg BW) were used in a completely randomized design. Steers were housed in 3 pens to receive the same diet and treatments from Exp. 1. Feed intake was measured using GrowSafe feed bunks, and indigestible neutral detergent fiber was used as the internal marker. In Exp. 1, a day effect was detected for plasmatic haptoglobin and glucose concentrations (P ≤ 0.04). In Exp. 2, no difference in DMI was observed (P = 0.88). Dry matter, organic matter, and acid detergent fiber digestibility in the total tract were reduced (P ≤ 0.05), whereas CP digestibility tended to decrease (P ≤ 0.07) in steers receiving PAP3 vs. CON and PAP1. Apparent total tract starch digestibility was increased (P ≤ 0.02) for PAP1 vs. PAP3. Neutral detergent fiber digestibility was greater (P < 0.01) for PAP1 vs. CON and PAP3. Feeding 1 g/d of a PAP against Streptococcus bovis, Fusobacterium necrophorum, and lipopolysaccharides increased fiber digestibility in backgrounding diets; however, further research is needed to understand the impaired responses on nutrient digestibility when greater doses are provided.